Modeling agro-hydrological surface-subsurface processes in a semi-arid, intensively irrigated river basin - Salam A. Abbas; Ryan T. Bailey; Jeffrey G. Arnold; Michael J. White; Ali Mirchi (Journal of Hydrology: Regional Studies)
Study region: Lower Arkansas River Basin (LARB) in Colorado, USA. Study focus: The process of implementing irrigation in large river basins often results in significant changes in hydrologic pathways and fluxes, such as canal seepage, runoff, recharge, pumping, and groundwater-river exchange. The objective of this study is to quantify the hydrologic fluxes in a highly irrigated river basin and investigate the controls on these fluxes, using the Lower Arkansas River Basin (LARB) (64,000 km2) in Colorado, USA as a demonstration case. We use the SWAT+ watershed model, enhanced with the new groundwater module gwflow, canal seepage, and irrigation application driven by daily canal diversions and groundwater pumping. The model is tested against streamflow and groundwater head, showing good performance along the Arkansas River and the alluvial corridor. New hydrological insights for the region: On average, precipitation in the basin is 380 mm/yr., of which 2 % (10 mm/yr.) becomes recharge and 2 % is irrigation (80 % surface water irrigation). Water yield is 18 mm/yr. (5 %), principally surface runoff and net groundwater discharge. Canal seepage is only 0.2 % of precipitation. Irrigation fluxes, canal and plant ET are highest in the downstream regions. Sensitivity analysis reveals the controlling watershed features on streamflow, groundwater head, and hydrologic fluxes for each region. Main parameters include streambed conductivity, plant uptake factors, snowmelt factors, aquifer properties, soil available water capacity, and soil percolation coefficient, with each parameter ranked by influence for each region within the basin. The calibrated models can be used to explore the impact of changes in climate, irrigation practices, and general water management schemes.